Evolutionary origins of intracellular symbionts in arthropods - Husník, Filip (Jihočeská univerzita, 2012)
Intracellular symbionts are widespread among arthropods, particularly within insects. Obligate symbiotic associations are known to have originated multiple times between the arthropods feeding on nutrient-poor diets and bacteria from various groups. However, exact phylogenetic positions and relationships among these symbiotic lineages are mostly unclear or vague. This thesis consists of an exemplary case study on the most symbiont-rich bacterial group, Enterobacteriaceae, already published in BMC Biology. It uses advanced phylogenetic tools and extended taxonomic sample to establish phylogenetic relationships among individual symbiotic lineages and their phylogenetic affinity to freeliving relatives. To provide it with broader background, the publication is accompanied by a review on general evolutionary forces influencing origin and maintenance of intracellular symbiosis in arthropods. Apart from overviewing the current known diversity of the symbiotic bacteria, it also points out specific drawbacks in inferring symbionts phylogeny and consequences that can phylogeny have on our understanding of intracellular symbiosis.
Evolutionary origins of intracellular symbionts in arthropods
Keywords: phylogeny; symbiosis; evolution; bacteria